Confirmation of the southern African distribution of the marine sponge Hymeniacidon perlevis (Montagu, 1814) in the context of its global dispersal - Toufiek Samaai; Thomas L. Turner; Jyothi Kara; Dawit Yemane; Benedicta Biligwe Ngwakum; Robyn P. Payne; Sven Kerwath (PeerJ, 2022)
Background Intertidal rocky shore surveys along the South African coastline (∼3,000 km) have demonstrated the presence and abundance of the encrusting orange sponge Hymeniacidon perlevis (Montagu, 1814), a well-known globally distributed species. After analysing the southern African populations, we gained a better understanding of the genetic structure of this now-accepted global species. Apart from confirming the presence of a single population of H. perlevis, we also determined its distribution in the southern African intertidal rocky shore ecosystem, compared its genetic diversity to congeners, predict its global distribution via environmental niche modelling, and discussed possible underlying mechanisms controlling the species’ global distribution. Methods We surveyed the South African coastline and sampled sponges at 53 rocky shore sites spanning over 3,000 km, from Grosse Bucht south of Lüderitz (Namibia) to Kosi Bay on the east coast of South Africa. DNA sequences of the nuclear rDNA internal transcribed spacer (ITS1) and the COI mitochondrial gene were obtained from 61 samples and compared them to a world-wide sample of other H. perlevis sequences. Using environmental predictor variables from the global dataset BIO-ORACLE, we predicted the probability of global occurrence of the species using an ensemble of eight distribution models. Results South African specimens were found to be 99–100% identical to other populations of H. perlevis (=H. sinapium) from other world-wide regions. The presence of a single population of H. perlevis in southern Africa is supported by genetic data, extending its distribution to a relatively wide geographical range spanning more than 4,000 km along the temperate southern African coast. The predicted global occurrence by ensemble model matched well with the observed distribution. Surface temperature mean and range were the most important predictor variables. Conclusion While H. perlevis appears to have been introduced in many parts of the world, its origins in Europe and southern Africa are unclear.